CONTRASTIVE ANALYSIS OF PHRASEOLOGISMS IN ENGLISH AND UZBEK MEDIA TEXTS - Shahrizoda Nuriddinova Akmal qizi (TADQIQOTLAR, 2025)
Abstract: Phraseologisms represent one of the most expressive layers of language and  play  a  particularly  significant  role  in  media  discourse.  This  article  presents  a contrastive analysis of phraseological units used in English and Uzbek media texts, focusing  on  their  lexical-semantic  characteristics,  structural  patterns,  pragmatic functions,  and  cultural  specificity.  Media  discourse  relies  heavily  on  figurative language  to  influence  public  opinion,  convey  evaluation,  and  ensure  emotional engagement, making phraseologisms a powerful linguistic tool. The study is based on materials collected from newspapers, online news portals, and analytical media articles in  both  languages.  Descriptive,  comparative,  and  contextual  analysis  methods  are applied. The findings reveal that while English and Uzbek media phraseologisms share universal  cognitive  mechanisms  such  as  metaphor  and  metonymy,  they  differ considerably in structural organization, stylistic preference, and cultural orientation. The  article  highlights  the  importance  of phraseological  competence  for  translation, media literacy, and intercultural communication.